2014
DOI: 10.2217/rme.14.60
|View full text |Cite
|
Sign up to set email alerts
|

Wharton’s Jelly Mesenchymal Stromal/Stem Cells Derived Under Chemically Defined Animal Product-Free Low Oxygen Conditions are Rich in MSCA-1 + Subpopulation

Abstract: Easy accessibility, abundance and genetic 'naivety' make WJ MSCs logistically a more attractive source for clinical applications than BM MSCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 35 publications
1
18
0
Order By: Relevance
“…Growing evidence indicate similar or superior proliferative capacity as well as maintenance of three-lineage differentiation ability and surface antigen expression of MSCs cultured in xeno-free media compared to standard serum-based conditions [1821], which was further supported by our results. However, the potential impact of such xeno-free media on the properties of MSC-EVs has not been studied.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Growing evidence indicate similar or superior proliferative capacity as well as maintenance of three-lineage differentiation ability and surface antigen expression of MSCs cultured in xeno-free media compared to standard serum-based conditions [1821], which was further supported by our results. However, the potential impact of such xeno-free media on the properties of MSC-EVs has not been studied.…”
Section: Discussionsupporting
confidence: 86%
“…Various chemically defined xeno-free media dedicated to support MSCs growth and characteristics have been offered on the market and their ability to maintain MSCs properties has already been confirmed [1821]. However, the impact of such media on the therapeutic properties of MSCs and MSC-derived EVs has never been studied.…”
Section: Introductionmentioning
confidence: 99%
“…The absence of MSCA-1 expression in WJ-MSCs could be associated with oxygen levels used during cell expansion 32 . For example, Devito et al showed a significant increase in the number MSCA-1 + cells within a WJ-MSCs population after in vitro expansion in low oxygen conditions 33 . www.nature.com/scientificreports www.nature.com/scientificreports/ The proliferation rate of MSCs differed depending on the tissue source.…”
Section: Discussionmentioning
confidence: 99%
“…MSCs were isolated at research laboratory grade standards. Briefly, cords were collected in PBS containing 40μg/ml of gentamicin [34]. Cords were cut into sections to expose the WJ, which was minced into fine pieces (1-3 mm 2 ).…”
Section: Hepatocyte and Msc Isolationmentioning
confidence: 99%